(untitled) (Journal of Hama University, 2025)
ABSTRACT The purpose of this study was to identify the relationship between the digital skills of the psychological counselor and his role in confronting Cyberbullying among secondary school students. For this purpose, the researcher prepared two reliable and validate questionnaires; One of them was to measure the role of the counselor in confronting cyberbullying, and the second one was to measure the level of digital skills. The sample consisted of (162) counselors from Lattakia Governorate, depending on the descriptive approach, during the academic year. (2023-2024) The researcher used SPSS to analyze the answers of the sample. The study showed many results, the most important of which are: There is statistically significant correlation between the scores of the sample members(psychological counselors) on the questionnaire for confronting cyberbullying and their scores on the digital skills questionnaire. This means that the psychological counselor’s abilities to confront cyberbullying increase by increasing the level of their digital skills. In light of this findings, the research presented many proposals, including: refining the digital skills of psychological counselors to enable them to activate their role in confronting cyberbullying.